2011
DOI: 10.1016/j.ejcts.2011.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Support time-dependent outcome analysis for veno-venous extracorporeal membrane oxygenation

Abstract: VV ECMO in patients suffering from severe lung failure is effective in improving gas exchange with an overall survival of higher than 50%. Prolonged need of ECMO support does not have an impact on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 23 publications
3
55
0
1
Order By: Relevance
“…Interestingly, the duration of ECMO support did not seem to be a negative predictor, as has been shown previously. 18 Cannulation sites were standardized, with the right femoral vein being used for drainage and the right internal jugular vein serving to return the arterialized blood. 19 Although the femoral vein was almost always accessible, central intravenous catheters or hemodialysis catheters sometimes hindered placement of the return cannula.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the duration of ECMO support did not seem to be a negative predictor, as has been shown previously. 18 Cannulation sites were standardized, with the right femoral vein being used for drainage and the right internal jugular vein serving to return the arterialized blood. 19 Although the femoral vein was almost always accessible, central intravenous catheters or hemodialysis catheters sometimes hindered placement of the return cannula.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported recovery after 48 [14], 52 [15], 56 [16], and 67 days [17] of ECMO support, with patients reported to have resumed their previous activity level. In addition, the largest series to date, by Camboni and associates [18], stratified patients by duration of ECMO and showed no significant difference in the survival of patients requiring ECMO for greater than 3 weeks, with an actual survival rate of 52%. These reports suggest that pulmonary recovery in the setting of long-term mechanical support for ARDS may be feasible.…”
Section: Commentmentioning
confidence: 97%
“…A single-institution retrospective review of 127 adult patients requiring ECMO for respiratory failure stratified patients on the basis of duration of ECMO support. 19 Overall survival to discharge was 51% with survival rates of 59% for patients requiring 10 days or less of ECMO, 31% for 11 to 20 ECMO days (n ¼ 32), and 52% for more than 21 ECMO days (n ¼ 19). Survival from P-ECMO (>21 days) in pediatric patients with respiratory failure was reported as 38%.…”
mentioning
confidence: 99%